Does Rabeprazole Sodium Alleviate the Anti-diabetic Activity of Linagliptin? Drug-Drug Interaction Analysis by In vitro and In vivo Methods - Hossain, Md. Jamal; Sultan, Md. Zakir; Rashid, Mohammad A.; Kuddus, Md. Ruhul (Drug Research, 2020)
Drug interaction has turned into the preeminent regarding issues for a prescriber during polypharmacy. The foremost objective of this research was to form a complex between linagliptin and rabeprazole sodium by in vitro interactions. The interactions between the drugs have been examined by monitoring some chromatographic and spectroscopic analyses viz. TLC, HPLC, FT-IR, UV, Job’s plot, conductometric titrations, and Ardon’s spectrophotometric strategy. Rabeprazole sodium formed a stable complex with linagliptin, which was ensured from the insight of these analytical data. The developed complex’s bright spot was clearly watched in the TLC plate. The retention time (Rt) of the formed complex was 5.303 min, where the Rt were 3.364 and 3.103 min for linagliptin and rabeprazole sodium, respectively, in HPLC chromatograms. In FT-IR and UV spectra of the formed complex revealed some disappearance of characteristic peaks that affirmed the complexation. All of the variations of the spectrophotometric and chromatographic properties from the antecedent drugs indicated the drug-drug interaction. Another crucial fact for the experimental aim was to affirm the assumed drug interaction by in vivo model examination. The assessment of anti-diabetic property on alloxan-induced Swiss albino mice proved significant in vivo interaction between the drugs. It was outlined from the animal study that the hypoglycemic activity of linagliptin might be significantly affected due to the complex formation of the drug with a proton pump inhibitor (PPI). Nonetheless, it is the primary outcome of the interaction, which recommends the bigger in vivo study or clinical monitoring on the human model.
Keywords: Drug interaction; Job’s plot; conductometric titrations; Ardon’s method; hypoglycemic property; TLC; HPLC; FT-IR; UV